The Theoretical Study of Photoemission from Various Region of Metal and Semiconductor - Kaphle, Gopi Chandra (Himalayan Physics, 2013)
This study involves the theoretical analysis of photoemission from the surface of metal(Al) and semiconductor (Si) in various regions. For the analysis of Photoemission, we calculated the vector potential with the help of dielectric model provided by Bagchi and Kar in modified form. From the calculation it is observed that electrons are mostly exited effectively at the surface regions than that of vacuum and bulk indicating that Photoemission takes place from the surface region, which favors the well accepted experimental and theoretical results. This study can be used to calculate photocurrent by the help of band structure of metals and semiconductors. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 46-50 Uploaded date: 12/23/2013